Pengaruhi Modal, Likuiditas , Efisiensi, Kinerja Terhadap Profitabilitas Pada Bank Umum Syariah Di indonesia - Vonny Tiara Narundana (LPPM STIE KRAKATAU, 2018)
Target This study aims to determine the effect of capital, liquidity, efficiency, banking performance on profitability in Islamic Commercial Banks in Indonesia in 2013-2015 This type of research is quantitative descriptive research. In this study using secondary data, and the period of time used is 3 years, namely the 2013-2015 period. The sampling technique was purposive sampling. The research variables consisted of 5 variables (4 independent variables and 1 dependent variable). The research data was taken from the monthly financial reports of the 2013-2015 period Islamic Commercial Banks. Validation of this research data was verified by publishing it on the website of each Islamic Commercial Bank. , the Bank Indonesia website and the Indonesian Central Statistics Agency website. Data analysis used is Regression analysis to analyze the factors that influence the profitability of Islamic Commercial Banks in Indonesia in 2013-2015. The results of the study are independent variables simultaneously (Test F) affect the profitability with a significant level of 0,000. While partially (t test) shows that: (1) capital has a positive and significant influence on profitability, (2) liquidity has a positive and significant influence on profitability, (3) efficiency has a negative and significant effect on profitability, (4) performance has a negative and significant impact on the profitability of Islamic Commercial Banks .. Based on the R² adjustment obtained 0.563 this means that the ability of four independent variables can explain Profitability 56,30 % while the remaining 43,70 % is explained by other factors.